Urinary excretion of albumin and retinol-binding protein during normal pregnancy. Issue 10 (October 1988) - Beetham, R; Dawnay, A; Menabawy, M; Silver, A
Abstract : In a cross sectional study of 88 pregnant women urinary excretion of albumin, when expressed as a ratio to creatinine concentration, was not significantly different from that in a non-pregnant control group of similar age (p greater than 0.05) and did not change significantly during pregnancy. Only when albumin excretion was expressed as a fractional clearance was the urinary excretion significantly increased in the third trimester compared with the first trimester (p less than 0.05), although it was still not significantly different from that in the non-pregnant control group. Excretion of retinol-binding protein was significantly increased during all three trimesters of pregnancy (p less than 0.01 in each case) and more so in the second and third trimesters than in the first. It is concluded that the increased total protein excretion that has been described during pregnancy is not explained by an increased excretion of albumin which remains essentially normal. In contrast, the tubular absorption of proteins is decreased.